SPR enhanced DNA biosensor for sensitive detection of donkey meat adulteration. (30th November 2020) - Mansouri, Maryam; Fathi, Farzaneh; Jalili, Roghayeh; Shoeibie, Shahram; Dastmalchi, Siavoush; Khataee, Alireza; Rashidi, Mohammad-Reza
Highlights: An SPR based DNA biosensor has been developed for detection of donkey meat marker. Gold nanostars was used as enhanced label in the sandwich hybridization assay. Target DNA could be detected with the LLOQ of 1.0 nM and RSD of 0.85%. The detection of 1% and 5% values of donkey meat adulteration was successfully done. Abstract: Herein, a surface plasmon resonance (SPR) enhanced DNA biosensor has been developed for real-time detection of donkey meat marker using biotinylated reporter and streptavidin functionalized gold nanostars (Stre@GNSs). Compared to the direct detection assay, this sandwich format for the enhancement of the signal, resulted in 6-folds orders increase in the sensitivity. Target DNA could be detected with the lower limit of quantification (LLOQ) of 1.0 nM with a relative standard deviation (RSD, n = 3) of 0.85%. In addition, the fabricated SPR sensor showed good selectivity for the target analyte over full complementary, single-base mismatch, three base-mismatch and non-complementary oligonucleotides. Finally, the proposed sensor was successfully applied for detection of donkey meat adulteration with various percentages in homemade beef sausage, as a real sample. The results indicated that the proposed biosensor provides a high specificity, easy, good sensitivity and fast approach for identification of donkey meat adulteration in food samples.